Educação ambiental e saber ambiental na Penitenciária Industrial de Caxias do Sul (PICS) - Sistema Prisional do Estado do Rio Grande do Sul - Toledo, Andreza de Souza (My University, 2016)
In the present paper it is proceeded the study of the Environmental Education and Environmental Knowing possibly developed in the Caxias do Sul's Industrial Penitentiary (CSIP) – Rio Grande do Sul's State Prison System – with the main goal to check the existence of instruments (legislative, operational and human) in the “NEEJANH” of CSIP, suitable and sufficient to produce an environmental education that makes it possible to prisoners achieve the acquisition of knowledge, social values, skills, attitudes and competencies, concerned with the conservations of the environment. Int his path, goes for research and analysis if the instruments (regulatory, operational and human) existing in “NEEJANH” of CSIP, related to environmental education and environmental knowledge, are suitable and sufficient in order to provide the production of environmental education and an environmental knowledge to enable, prisoners, the acquisition of knowledge, social values, skills, attitudes and competencies, concerned with the conservations of the environment, identifying, if applicable, the effective contributions of these instruments available to the CSIP. Fot this it is used the type of descriptive research (documentary and bibliographic), and the scientific approach methods: deductive and hypothetical-deductive. From this research, it was found that these instruments are not suitable and sufficient to enable prisoners to acquire knowledge, social values, skills, attitudes and skills, ie the production of environmental education and an environmental knowledge concerned with the conservation of the environment, although, in most cases, these instruments are in compliance with the legal requirements specified by the National Policy and State Environmental Education. Thus, it is possible to infer that both these instruments should be improved as some normative provisions of these public policies should be reviewed and improved, so that the legal objectives of environmental education can be effectively implemented so that an education are effectively produced environmental and environmental knowledge concerned with the conservation of the environment, purpose is defined by these public policies, in line with the Federal Constitution of 1988.
No presente trabalho procede-se ao estudo acerca da Educação ambiental e do Saber Ambiental eventualmente desenvolvidos na Penitenciária Industrial de Caxias do Sul (PICS) -Sistema Prisional do Estado do Rio Grande do Sul, tendo por principal norte a verificação quanto à existência de instrumentos (legislativos, operacionais e humanos), no NEEJANH da PICS, aptos e suficientes para produzir uma educação ambiental que possibilite, aos presos, a aquisição de conhecimentos, valores sociais, habilidades, atitudes e competências, voltados para a conservação do meio ambiente. Nessa senda, parte-se para a investigação e análise se os instrumentos (normativos, operacionais e humanos) existentes no NEEJANH da PICS, relacionados à educação ambiental e ao saber ambiental, são aptos e suficientes no sentido de propiciar a produção de uma educação ambiental e de um saber ambiental que possibilitem, aos presos, a aquisição de conhecimentos, valores sociais, habilidades, atitudes e competências, voltados para a conservação do meio ambiente, identificando, se for o caso, as efetivas contribuições dos referidos instrumentos de que dispõe a PICS. Para tanto, utiliza-se a tipologia da pesquisa descritiva (documental e bibliográfica), bem como os métodos científicos de abordagem: dedutivo e hipotético-dedutivo. A partir dessa pesquisa, constatou-se que esses instrumentos não são aptos e suficientes para possibilitar, aos presos, a aquisição de conhecimentos, valores sociais, habilidades, atitudes e competências, ou seja, a produção de uma educação ambiental e de um saber ambiental voltados para a conservação do meio ambiente, embora, em sua maioria, esses instrumentos estejam em conformidade com as exigências legais especificadas pelas Políticas Nacional e Estadual de Educação Ambiental. Sendo assim, é possível depreender-se que tanto esses instrumentos devem ser aperfeiçoados quanto algumas disposições normativas dessas Políticas Públicas devem ser revistas e aprimoradas, a fim de que os objetivos legais da educação ambiental possam ser efetivamente concretizados, para que sejam efetivamente produzidos uma educação ambiental e um saber ambiental voltados para a conservação do meio ambiente, finalidade esta definida por essas Políticas Públicas, em consonância com a Constituição Federal de 1988.
Keywords: Penitenciária Industrial de Caxias do Sul; Educação ambiental; Política pública; Direito ambiental; Prison of Caxias do Sul Industrial; Environmental education; Public policy; Environmental law